Local and systemic eosinophilia in patients with nasal polyps - Pradhananga, RB; Shrestha, A; Pradhan, B; Adhikari, RC (Journal of Institute of Medicine Nepal, 2009)
Background: To determine the presence of local and systemic eosinophilia in patients with nasal polyps and to correlate between them. Materials and Methods: Patients of all age group, presented in ENT OPD during October 2004 to May 2006, with ethmoidal polyps were studied. Patients using steroids in last one month, antrochoanal polyps and histopathological diagnosis other than nasal polyps were excluded. The local eosinophils count in nasal polyp tissue of study group and inferior turbinate mucosa of control group were evaluated and analyzed. Similarly absolute blood eosinophil counts in both study and control group were evaluated. The association between local and systemic eosinophilia were analysed. Results: Out of 78 patients with nasal polyps systemic eosinophilia was seen in 28 patients (35.9%) and local eosinophilia was seen in 50 (64.1%) patients. Among 30 patients of control group only 2 patients (6.7%) had systemic and none had local eosinophilia. On analyzing the results, the presence of systemic and local eosinophilia in patients with polyps were statistically significant with p value 0.005 and 0.0001 respectively. The association between them was also significant (p<0.025). Conclusion: There is significant local and systemic eosinophilia in patients with nasal polyps and also significant correlation between them. Key Words: Nasal polyps, Absolute blood eosinophilia, Local eosinophilia. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 8-12